Pengaruh Perbandingan Daging Sapi dan Ubi Ungu (Ipomoea Batatas Blackie) Terhadap Karakteristik Patty Burger - Felicia, Michelle; Indri Hapsari Arihantana, Ni Made; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i02.p04a, 2024)
Burgers are one of the most popular fast foods among the public. Fast food generally contains large amounts of fat, sugar, salt and calories, but is low in vitamins, minerals and fiber. Therefore, an innovation is needed for the hamburger patty product with the addition of purple sweet potato to increase the nutritional content which is rich in fiber and good compounds such as antioxidants. This study aimed to determine the comparison of the effects of beef and sweet purple potato on the chemical characteristics of the hamburger patty. The design method used was a completely randomized design with one treatment factor, namely the comparison between beef patty and purple sweet potato 100%:0%, 90%:10%, 80%:20%, 70%: 30%, 60%:40% and 50%:50%. This search was repeated 3 times, resulting in 18 experiments. The data obtained were analyzed with the Analysis of Variance and, if the treatments had a significant effect, the Duncan Multiple Range Test was continued. The result showed that the comparison between beef and purple sweet potato had a significant effect on water content, protein content, fat content, crude fiber content, pH level, water holding capacity, cooking loss, anthocyanin value, antioxidant activity, color, aroma, texture, taste and general acceptance. The 70%:30% ratio produced the best hamburger patty characteristics with 25.38% water content, 13.97% protein content, 11.87% fat content, 5.65% crude fiber, pH level 5.77, 37.63% water holding capacity, 22.59% cooking loss, anthocyanin value of 17.14 mg/L and antioxidant activity of 27.21%. The color sensory characteristics were liked, the aroma was mildly liked, the texture was tender and liked, the taste was typical of beef and liked, and the overall acceptance was liked.